ANALISIS FENOMENA FLEXING PADA VIDEO SULTAN MEDAN BELI MOBIL LISTRIK TESLA JAM 3 PAGI!! #MURAHBANGET DI KANAL YOUTUBE INDRA KENZ - Firstiyanti, Aulia (Asosiasi Dosen Muda Indonesia, 2023)
We live in a world where status is determined by wearing a logo, driving a sports car, and/or listening on AirPods. This is closely related to the role of social media and conspicuous consumption. This consumption model is called flexing by today's virtual world community. In this study, the authors analyzed the phenomenon of flexing (show-off culture) and packaged it in a journal entitled Flexing pada Video Sultan Medan Beli Mobil Listrik Tesla Jam 3 Pagi!! #MurahBanget di Kanal YouTube Indra Kenz. The writer tries to examine flexing symbols using Charles Sanders Peirce's semiotics. This study applies qualitative methods by sorting and selecting qualified data and then analyzing it. The conclusion is that the representation of conspicuous consumption contained in the video